Arthroscopic treatment of reverse Hill-Sachs injury avoiding internal fixation: Case report - Jaramillo Fernández, Juan Carlos; Arismendi Montoya, Andrés; Duque Orozco, María del Pilar (Revista Colombiana de Ortopedia y Traumatología, 2014)
Traumatic posterior shoulder joint dislocation associated with a Hill-Sachs fracture is still considered a rare condition, but yet, surgical treatment is a challenge for shoulder surgeons. The majority of currently described surgical techniques aim to modify proximal humeral anatomy and are complex procedures. Herein we describe a minimal invasive surgical technique, consisting of an arthroscopic-guided percutaneous fracture disimpaction without the use of any fixation device for permanent reduction. A case report is presented of a patient with a reverse Hill-Sachs lesion after a traumatic posterior dislocation, treated arthroscopically without the use of any type of osteosynthesis materials.